Pengaruh Price, Brand Image Dan Pelayanan Terhadap Kepuasan Pelanggan Indihome Pada PT Telkom Witel Metro - Birlianto, Ali Rahmat; Imantoro, Jati (Universitas Muhammadiyah Metro, 2022)
INFLUENCE OF PRICE, BRAND IMAGE AND SERVICE ON INDIHOME CUSTOMER SATISFACTION AT PT TELKOM WITEL METRO By Ali Rahmat Birlianto ,H. Suwarto2, S.E M.M, Jati Imantoro, S.E., M.E.Sy NPM.16610134 ABSTRACT Ali Rahmat Birlianto The Influence of Price, Brand Image And Service On Indihome Customer Satisfaction At Pt Telkom Witel Metro. Supervisor (1) H. Suwarto, S.E M.M (2) Jati Imantoro, S.E., M.E.Sy. Today's increasingly rapid technological development and competition requires every company to innovate for the sake of its company's existence. The existence of innovation in the company makes the company can grow and be able to compete in the market. The development of technology and information is getting higher and more complex. One of the products that has developed quite rapidly is pay television service products. This study aims to determine 1) To determine the effect of Price on customer satisfaction of Indihome products from PT. Telkom Witel Metro.2) To determine the effect of brand image on customer satisfaction of Indihome products from PT. Telkom Witel Metro 3) To determine the effect of customer service on customer satisfaction of Indihome products from PT. Telkom Witel Metro. 4) To determine the effect of price, brand image and customer service on customer satisfaction of Indihome products from PT. Telkom Witel Metro. The survey method was chosen as the primary data source. The survey method focuses on collecting data from respondents who have certain information, thus enabling researchers to solve problems. Data collection was carried out using a questionnaire or questionnaire instrument. In this study, the population is consumers who use telkom products. The sampling technique uses accidental sampling with a total sample of 100 people. Data collection techniques using a questionnaire with a Likert scale. The results showed that 1) there was a positive and significant influence between Price on Indihome product customer satisfaction 2) there was a positive and significant influence between brand image on Indihome product customer satisfaction. 3) there is a positive and significant influence between service on customer satisfaction for Indihome products. 4) there is a positive and significant influence between price, brand image and service on customer satisfaction of Indihome products. Keywords: Price, Brand Image, Service and Customer Satisfaction